Supplementation of Psidium guajava (Guava) fruit polysaccharide attenuates paracetamol-induced liver injury by enhancing the endogenous antioxidant activity - Aspalilah Alias,; Faizah Othman,; Abdul Rashid Li,; Aqilah Kamaruddin,; Rafizul Yusof,; Farida Hussan, (Universiti Kebangsaan Malaysia, 2015)
This study was aimed to determine the effect of polysaccharide from guava fruit on paracetamol (PCM)-induced liver injury. Aqueous extract of Psidium guajava fruit was treated with 95% ethanol to collect the water soluble polysaccharide precipitates. Thirty-eight male Sprague Dawley rats were divided into control (C), PPG400, PCM, PPG200+PCM and PPG400+PCM. The control and PCM groups received 0.9% normal saline orally while the rest were given 200 and 400 mg/kg of freeze-dried polysaccharide (PPG) per oral for fourteen days. At day 15, the animals were orally received PCM (2 g/kg) except the control and PPG400 groups which received 5% dimethyl sulfoxide. At day 16, the blood was collected to determine serum liver enzymes such as transaminases (AST and ALT). The liver tissue was harvested for determination of superoxide dismutase (SOD), glutathione (GSH), tumour necrosis factor-α (TNF-α), interleukin-6(IL6), microscopic changes and glycogen content. The PCM group showed significant higher level of AST, ALT, TNF-α and IL6 than those of group C. The PCM group showed glycogen depletion, vacuolisation, loss of cell membrane, inflammatory cells infiltration and distorted hepatocelluar cords and narrow sinusoidal spaces. However, those PCM-induced alterations were attenuated by the PPG supplementation. Therefore, the polysaccharide of Psidium guajava possesses hepatoprotective activity and can be used as a dietary supplementation for protection of liver.